Liberation Theology Perspective toward Political Involvement of the Church: A Theological Evaluation - Budi Harwanto; Tauran Edgar (Fakultas Filsafat Universitas Advent Indonesia, 2025)
This article critically examines liberation theology’s perspective on the Church's political involvement, with a particular focus on its Latin American origins, hermeneutical foundations, and theological implications. Rooted in the socio-political struggles of the mid-20th century, liberation theology emerged as a response to systemic poverty, oppression, and injustice, advocating for the Church’s active engagement in transforming unjust social, economic, and political structures. Drawing on key theologians such as Gustavo Gutiérrez, Leonardo Boff, and Jon Sobrino, this study analyses the movement’s use of biblical narratives—particularly the Exodus—and its interpretation of Jesus’ ministry as inherently political. Employing a descriptive-evaluative methodology through library research and critical analysis of primary and secondary sources, the article explores how liberation theology redefines salvation as historical praxis and the Kingdom of God as a call to revolutionary justice. While affirming the movement’s prophetic emphasis on the preferential option for the poor, the article also critiques its potential reductionism in biblical hermeneutics and its tension with traditional ecclesial understandings of Christ’s apolitical mission. The discussion concludes that while liberation theology offers a necessary corrective to ecclesiastical detachment from suffering, its political framework requires careful integration with broader theological themes such as sin, grace, and eschatology to avoid ideological captivity. This evaluation contributes to contemporary theological discourse by offering a balanced assessment of liberation theology’s enduring relevance and limitations.